Determining the Propensity for Accounting Fraud: The Role of Internal Control, Regulatory Compliance, and Unethical Behavior - Imanita Septian Rusdianti (Trescode Green Organization, 2026)
The tendency of accounting fraud is a serious risk that can harm an organization economically and reduce stakeholder trust. This phenomenon is not only related to weaknesses in the accounting system, but is also influenced by the behavioral aspects of individuals within the organization. This study aims to analyze the influence of internal control, compliance with accounting rules, and unethical behavior on the tendency of accounting fraud at PT Ciomas Adisatwa Tbk, East Java Region I, Malang. The study used a quantitative approach with primary data obtained through questionnaires to 68 respondents involved in accounting and administrative functions. Data analysis was performed using multiple linear regression after going through validity, reliability, and classical assumption tests. The results of the study indicate that internal control and compliance with accounting rules do not significantly influence the likelihood of accounting fraud. Conversely, unethical behavior has been shown to have a positive and significant effect on the likelihood of accounting fraud. This finding indicates that individual behavioral factors play a more dominant role than structural aspects in triggering fraud. This study implies that fraud prevention efforts need to be implemented through an integrated approach that includes strengthening control systems, procedural compliance, and internalizing ethical and integrity values ​​to achieve sustainable and accountable corporate governance.